Swelling and Salt Formation in Ibuprofen and Tranexamic Acid-Containing Tablets during High-Temperature Storage - Yuto Kawano; Yoshiharu Tanaka; Nanami Hata; Yuki Yoshiike; Masato Nakajima; Etsuo Yonemochi; Nobuhiro Ishihara (Crystals, 2022)
Ibuprofen (IBP)- and Tranexamic acid (TXA)-containing tablets are known to swell when stored at high temperatures, but the mechanism of swelling is unknown. In this study, we investigated the possible mechanism of swelling with high-temperature storage. Differential scanning calorimetry (DSC) and powder X-ray diffractometry (PXRD) analyses showed that a new complex was formed in swollen tablets, when stored at 50 °C for 60 days. Additionally, we prepared single crystals of IBP and TXA, and analyzed them using single crystal X-ray diffractometry (SCXRD), to identify the new complex formed during storage. This revealed that the single crystal was a salt consisting of IBP and TXA. The PXRD peak of the salt simulated by SCXRD matched that of the PXRD peak of the swollen tablet after storage. These results suggest a close relationship between the swelling and crystal structures of IBP and TXA.